Power outages and refrigerated medicines: The need for better guidelines, awareness and planning. (13th June 2018) - Kosari, S.; Walker, E. J; Anderson, C.; Peterson, G. M.; Naunton, M.; Castillo Martinez, E.; Garg, S.; Thomas, J.
Summary: What is known and objective: Vaccines and other pharmaceuticals are essential medical supplies that require continuous storage at specific temperatures to maintain viability. Power outages can lead to a break in the cold chain, resulting in the degradation of essential medicines. Comment: After a power outage, the stability of vaccines and other medicines can be difficult to ascertain. Many public health guidelines therefore recommend discarding potentially compromised pharmaceuticals unless the cold chain can be guaranteed—a costly endeavour. There are government guidelines aimed at minimizing exposure to high temperatures in the event of a power outage; however, the usefulness of these guidelines is uncertain. What is new and conclusion: The actual cost of vaccine and pharmaceutical loss due to a break in the cold chain is poorly studied and requires further research. Additional recommendations regarding the stability of specific medicines would also be a valuable resource. Abstract : The loss of vaccines and other pharmaceuticals due to cold chain breaches, is likely to present a significant financial burden worldwide. There is a need for investment in stability testing of specific pharmaceutical products, along with the development of more comprehensive and useful guidelines for health professionals to manage cold chain breaches.